Facile and diastereoselective synthesis of 3, 2′-spiropyrrolidine-oxindoles derivatives, their molecular docking and antiproliferative activities. Issue 2 (15th January 2015) - Kathirvelan, D.; Haribabu, J.; Reddy, B.S.R.; Balachandran, C.; Duraipandiyan, V.
Graphical abstract